EFEKTIVITAS TIKTOK DAN INSTAGRAM SEBAGAI SUMBER LITERASI KEUANGAN BAGI CALON INVESTOR MUDA DI KOTA BENGKULU - Meibie; Evan Setiawan; Yetti Afrida Indra (JSE: Jurnal Sharia Economica, 2026)
The development of digital technology has changed the way people obtain financial information through social media, particularly TikTok and Instagram. This study aims to analyze the effectiveness of both platforms as sources of financial literacy for prospective young investors in Bengkulu City. The study used a descriptive qualitative approach involving 20 purposively selected informants. Data were collected through an open-ended questionnaire using Google Forms and analyzed using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results show that TikTok and Instagram are effective in improving financial literacy by providing information that is easily accessible and understandable. TikTok excels through engaging short videos, while Instagram is more effective in presenting material systematically through infographics and carousel features. Both platforms increase financial knowledge and investment awareness. However, users still need to verify information through credible sources before using it as the basis for investment decisions